2021
DOI: 10.1590/0001-3765202120191453
|View full text |Cite
|
Sign up to set email alerts
|

Allele Specific Expression (ASE) analysis between Bos Taurus and Bos Indicus cows using RNA-Seq data at SNP level and gene level

Abstract: In the current study, allele specifi c expression analysis was performed in two subspecies cows (Bos taurus and Bos indicus) at SNP and gene levels. RNA-Seq data of 21,078,477 and 20940063 paired end reads from pooling of whole blood samples (Leukocyte) from 40 US Holstein (Bos Taurus) and 45 Cholistani cows (Bos indicus) obtained from SRA database in NCBI. Quality control and trimming of row RNA-Seq data were processed by FASTQC and Trimmomatic softwares. The transcriptome was assembled by TopHat2 software in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As our research group [ 8 , 9 ] and others reported, ASE is widespread in bovine [ 4 , 6 , 8 , 10 , 11 ]. Previously, we described a high coverage list of single nucleotide polymorphisms (SNPs) located in transcripts with ASE (ASE SNPs) distributed in Nelore ( Bos indicus ) muscle and the candidate cis -regulatory variants potentially affecting the allelic expression.…”
Section: Introductionmentioning
confidence: 83%
“…As our research group [ 8 , 9 ] and others reported, ASE is widespread in bovine [ 4 , 6 , 8 , 10 , 11 ]. Previously, we described a high coverage list of single nucleotide polymorphisms (SNPs) located in transcripts with ASE (ASE SNPs) distributed in Nelore ( Bos indicus ) muscle and the candidate cis -regulatory variants potentially affecting the allelic expression.…”
Section: Introductionmentioning
confidence: 83%
“…In diploid organisms, allele specific expression (ASE) provides strong evidence that genes may be under differential cis-regulatory control [26,27]. Using a method that has been applied to a variety of taxa [26,[28][29][30][31][32] but not mosquitoes, we describe the identification of genes showing ASE in An. gambiae which potentially confer metabolic resistance.…”
Section: Introductionmentioning
confidence: 99%